Seroprevalence of cytomegalovirus and its coinfection with Epstein-Barr virus in adult residents from Manaus: a population-based study - Gustavo Magno Baldin Tiguman; Laura Beatrice Poll; Carlos Eduardo de Castro Alves; Gemilson Soares Pontes; Marcus Tolentino Silva; Tais Freire Galvao (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: This study assessed the seroprevalence of cytomegalovirus, associated factors, and Epstein-Barr virus coinfection among adult residents of Manaus. METHODS: Using a cross-sectional study design, we collected blood samples from 136 individuals in a household survey in 2016. Prevalence ratios were calculated using Poisson regression. RESULTS: Cytomegalovirus and Epstein-Barr virus seroprevalences were 67.6% (95% CI: 9.7-75.6%) and 97.8% (95% CI: 95.3-100.0%), respectively. Coinfection was observed in 66.2% (95% CI: 58.1-74.2%) of participants. Bivariate analysis showed no statistical association. CONCLUSIONS: Seroprevalences were high among participants and approximately 7 out of 10 individuals had cytomegalovirus and Epstein-Barr virus coinfection.